One owner’s perspective after a pet hospice journey - Allison C. Hudock (Human-Animal Interactions)
Abstract I was the sole pet parent to my beloved cat, Peaches, who received a devastating advanced cancer diagnosis in June 2023. Upon my decision not to pursue chemotherapy for Peaches, I became her sole hospice caregiver in the subsequent months until her death in November 2023. This commentary provides my perspective as a pet parent and caregiver during the time of a traumatic life-limiting diagnosis, my decision to pursue hospice care over treatment, the challenges of navigating hospice care as a sole caregiver without adequate support, and my hindsight and takeaways since her passing.